THE REFORM AND DEVELOPMENT SYSTEMS OF HIGHER EDUCATION IN AFRICAN ANGLOPHONE COUNTRIES - Mahgoub, Yassir M; Alawad, Abeer A (European Scientific Journal, ESJ, 2014)
The paper presented is based on a comprehensive research approach to help enhancing reform and development systems of Higher Education in African countries. And this involved undertaking a desktop review to determine the current trends and initiatives internationally and in Africa. In addition, a limited number of interviews have been held with individuals to provide further input. Finally, the entire strategy was discussed at an Experts’ meeting held in Zhejiang Normal University (China) in August, 2012. And the descriptive analytical and experimental methods are used in this research. The results of the study are expected to be beneficial for the reform development systems of higher education programs in the African countries. The study sample consists of (30) participants coming from the African Anglophone countries. There are topics of the reform and development systems of Higher Education in African countries were prepared depending to highlights on current status of higher education and, higher education environment and higher education challenges and considers some of the key challenges and opportunities that may need to be considered in developing a framework for harmonization of higher education programs across Africa. The Conclusion showed there are African countries must urgently reform and develop systems and implement higher education policies aimed at expanding student enrolments, strengthening quality and the qualifications of academics, at least doubling the production of postgraduates, developing research capability and changing how universities work including improving governance and planning. The researchers recommend the scale up and modernize the higher education systems through ICT infrastructure.